On differentiability of mappings of finite-dimensional domains into Banach spaces - Bondar, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
The well-known Stepanov criterion of the differentiability (approximate differentiability) of real functions is generalized to mappings of subsets of $R^n$ n into Banach spaces satisfying the Rieffel sharpness condition, in particular, reflexive Banach spaces. For Banach spaces that do not satisfy the Rieffel sharpness condition, this criterion is not true.